FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN FUNGSI PARU PADA PEDAGANG TETAP DI TERMINAL BUS SENEN JAKARTA PUSAT TAHUN 2019 - Yenita Anggraini, (2020)
Complaints of pulmonary function are the inability to develop (elasticity) of the pulmonary organs as well as structural abnormalities (anatomically) or functionally that can cause slowing of respiratory air flow. Based on the results of the prevalence of the ILO in 2013 stated that in developing countries workers affected by pneumoconiosis as much as 30% to 50%. The purpose of this study was to determine the factors associated with complaints of lung function in permanent traders in the Senen Bus Terminal in Central Jakarta in 2019. Data collection methods used to measure PM2.5 using the Dustrak Environmental Air Monitor conducted by officers from the Central Jakarta K3 Center and the method for checking lung function tests using a spirometer performed by a Professional Doctor from the Central Jakarta K3 Center. The instrument used in this study was to use a pulmonary function check tool that is a spirometer with a spiro analyzer type AS-505 Minato Japan, using a PM2.5 measurement tool that is Dustrak Environmental Air Monitor and using a questionnaire with the form of open questions. The results of the research that have been obtained will be carried out by univariate analysis and bivariate analysis. The results of this study are that there is no significant relationship between individual characteristics, behavioral factors, occupational factors and environmental factors with complaints of lung function in permanent traders at the Senen Bus Terminal in Central Jakarta in 2019.